Exploring reward effects in experimental syntax - Rui P. Chaves (Linguistic research, 2025)
Experimental Syntax research often involves participants reading or listening to disconnected sentences which are often unusual in some way. Such tasks are rather artificial and involve assigning numbers to sentences, or pressing keys to reveal the next word on a screen. Some participants may lack motivation to process these sentences in a typical way, given these unusual settings, which can lead to data that may not reflect normal language processing. Specifically online and offline measures of comprehension may be affected by not only task demands but also participant motivation. In the present study we manipulate the amount of reward for completing such tasks in order to examine how it impacts (if at all) the experimental outcomes. This is an important question to explore as there are currently no compensation standards in experimental linguistics, with some studies paying subjects with rates above the minimum wage, and others offering course credit instead of financial compensation. The present paper uses reward magnitude as a proxy to motivation to perform a task. The results suggest that reward incentives can impact outcomes, but only subtly so, at least for the populations tested in this study. Additionally, there is a significant degree of variation across studies, suggestive of participants sometimes deploying strategies to maximize the chances of completing the task appropriately, but in the process create artificial patterns in the data. KCI Citation Count: 0